PENERAPAN METODE BERNYANYI DAN MEDIA FLASH CARD UNTUK MENINGKATKAN DAYA INGAT ANAK DALAM PENGENALAN HURUF HIJAIYYAH DI TPA DARUL FALAH GAMPONG PINEUNG - Mashuri Mashuri; Maya Dewi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2017)
Singing method is one of the learning method that is expected for students to be able and remember the material well. Methods diekkan, media is also important to improve memory. One is flashcard media. By using both of these systems, the learning process will attract and stimulate learners' recollection of the letters of hijaiyah recognition. Based on preliminary observations, reduce the memory in the introduction of similar or similar hijaiyyah letters in Darul Falah Gampong Pineung Landfill, so further efforts / treatment is how to apply the method of singing and flashcard media. This research uses PTK (Classroom Action Research) approach. The results showed that the learning method and flashcard media in the introduction of hijaiyyah letters to learners experienced a significant improvement. The application of singing methods and using flashcard media proved to improve the memory of learners and can distinguish what is meant in the material introduction hijaiyah.